The Impact of Electronic Banking Services Development on Financial Inclusion in Jordan - Hejazeen, Rami; Yamin, Ismail Younes (Journal of Ecohumanism, 2024)
This study examined the impact of the development of electronic banking services on financial inclusion, and the study population consisted of operating banks in Jordan. The sample of the study relied on a comprehensive survey due to the small size of the sample; its data were extracted for the period from (2015) to (2022). The study examined the impact of the development of electronic banking services in its various dimensions (diversity of electronic banking services, electronic banking services provided by ATMs, mobile financial services, and the Internet) on financial inclusion in Jordan in its dimensions (access to banking services, use of banking services, availability of banking services). The study followed the descriptive analytical approach using E-Views program in order to describe the data and estimate the study model to test the hypotheses of the study. The study found that there is a statistically significant positive impact of the development of electronic banking services in its various dimensions on financial inclusion in Jordan in its various dimensions. The researcher recommended the need to support research and innovation in the field of financial technology and develop new and innovative electronic banking services to meet the needs of customers and enhance financial inclusion, and recommended enhancing the diversity of services Banking, the access to banking services, and the financial literacy, and recommended to conduct future studies related to the role of the of electronic banking services development on financial inclusion.